Eco-positioning of airlines: Perception versus actual performance. (May 2015) - Mayer, Robert; Ryley, Tim; Gillingwater, David
Abstract: To date there has been little research in air transport into the eco-positioning of airlines, that is, their environmental image relative to other airlines and how actual environmental performance relates to this eco-positioning. This paper identifies the environmental perceptions that passengers hold of twelve airlines and relates these perceptions to airlines' actual environmental performance, using load factors, aircraft age and the atmosfair Airline index as proxies for environmental performance. Based on a survey of over 600 passengers at Liverpool John Lennon Airport, the research analyses air travellers' perception of airlines from an environmental perspective. The results show that while there are significant differences in people's environmental perception of airlines, the eco-positioning of the airlines is not correlated to their actual environmental performance. The results support previous research findings in other industries that in many cases actual performance is less important than communicating environmental messages to the public in creating a superior eco-positioning. Highlights: Environmental performance indicators are compared with airlines' eco-positioning. The atmosfair Airline Index has no significant effect on airlines' eco-positioning. Airlines with higher load factors do not hold a better eco-positioning. Airlines with a lower average aircraft age do not hold a better eco-positioning.